A study of Opinions of Agricultural Entrepreneurs in Hiring Migrant Workers of Burmese Nationality : A Case Study of Mae Sot District Tak Province - Jinta , Watchara; Wongwatthanaphong , Kampanart (Journal of Modern Learning Development, 2021)
This research aims to study To study the causes of foreign labor hiring of entrepreneurs in the agricultural sector To compare opinions of agricultural entrepreneurs towards hiring foreign workers And to study problems and obstacles in employment of foreign workers of agricultural operators In the area of ​​Mae Sot District, Tak Province, quantitative research. From questionnaires distributed to 390 entrepreneurs and a qualitative research. Ten key informants were interviewed using descriptive statistics to find the distribution of frequency, percentage, mean and standard deviation. The results showed that 1) opinions of agricultural sector operators towards hiring foreign workers. 2) Agricultural entrepreneurs with different sex, age, education, monthly income had opinions on hiring of migrant workers in Mae Sot District, Tak Province by classification. Personal factors 3) Problems and obstacles for agricultural entrepreneurs in hiring foreign workers with Burmese nationality: A case study in Mae Sot District, Tak Province, it was found that labor barriers were the number one problem followed by social obstacles. And problems and obstacles in politics and law Last